(untitled) (Raparin Journal of Humanities (RJH), 2022)
The research is focused on urban distribution analysis in the terms of location, pattern, and expansion, in addition to the causes of change and development of the cities have taken into account. The inductive method has been used based on quantitative, statistical, and cartographical approaches such as Lorenz’s Curve, Moran’s Index, chi square And Nearest Neighbor Analyses for distribution pattern, Robinson’s Equation for distance measurement between cities, and area belt for spreading and gathering measurement of the cities. The study is concluded that the taken cities in the study haven’t irregular patterns instead they are spread under the effect of natural and human factors.